Investigation of co-existing bacteria in platelets by employing long-term culturomics and metagenomics - Wang, Qiqi; Zhao, Mengyi; Liu, Anqing; Zhao, Yuwei; Fan, Zhenxin; Huang, Yang; Gao, Zhan; He, Miao (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBacterial contamination of platelets presents a substantial risk in transfusion medicine. Conventional detection approaches have limitations in sensitivity and bacterial coverage. In this study we employed culturomics and metagenomics to investigate co-existent bacteria in platelets, aiming to enhance transfusion safety and explore healthy bacteremia.MethodsPlatelet from 6 healthy donors underwent a 30-days extensive cultivation and isolation procedure using in-house culturomics.Results16S rRNA sequencing identified 90 bacterial strains across 3 phyla, 5 classes, 5orders, 7 families, 9 genera, and 23 species. Metagenomics sequencing revealed greater microbial diversity, detecting an average of 3018 microbial species per sample. The bacteria concurrently detected by both culturomics and metagenomics included species from Firmicutes, Actinobacteria, and Proteobacteria.DiscussionThis combined approach validates the presence of bacteria in platelets, likely originating from the skin, gut, oral cavity, environment, or bloodstream, providing a comprehensive strategy for bacterial identification in transfusion products.